Efficacy of using cytoflavin and L-lysine escynate in complex treatment of anterior ischemic neuropathy (Ukrainian Journal of Ophthalmology, 2026)
Introduction. The problem of the treatment of anterior ischemic neuropathy is quite important in modern ophthalmology. Purpose. The paper studies the effectiveness of the combination of drugs cytoflavin and L — lysine escynate in patients with anterior ischemic neuropathy. Material and methods. Clinical studies were performed in 20 patients (20 eyes) with anterior ischemic neuropathy in treatment which used a combination of cytoflavin and L — lysine escynate. The control group consisted of 20 patients (20 eyes) who were treated without these drugs. The efficacy of treatment was assessed by visual acuity, field of vision, optical coherence tomography of the optic nerve. Visual functions were studied on discharge, 1 month and 6 months after treatment. Results. In the group under study visual functions were above 17 % after treatment compared with the controls. Swelling of the optic nerve decreased in 95 % of patients of the main group and in 75 % of patients in the control group. After 1 month after treatment, a statistically significant change in visual functions has not occurred either in the main or in the control groups. But all functional parameters were significantly higher in the group under study. Papilledema was persisted in 65 % of patients of the main and 85 % of patients in the control group. After 6 months of treatment in both groups, there was a deterioration of visual functions compared with those on discharge (not statistically significant). However, in the study group visual functions were by 23 % higher than in the control group. Conclusions. Immediate and long-term results of treatment of patients with anterior ischemic neuropathy and control group allowed to make a conclusion that the use of a complex treatment with infusions of cytoflavin and L-lysine escynate allows to increase significantly the effectiveness of treatment of this disease.
Keywords: anterior ischemic neuropaty; Cytoflavin; L — Lysine Aescinatis; efficiency